2008
DOI: 10.1038/onc.2008.195
|View full text |Cite
|
Sign up to set email alerts
|

Gene array analysis reveals a common Runx transcriptional programme controlling cell adhesion and survival

Abstract: The Runx genes are important in development and cancer, where they can act either as oncogenes or tumour suppressors. We compared the effects of ectopic Runx expression in established fibroblasts, where all three genes produce an indistinguishable phenotype entailing epithelioid morphology and increased cell survival under stress conditions. Gene array analysis revealed a strongly overlapping transcriptional signature, with no examples of opposing regulation of the same target gene. A common set of 50 highly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 45 publications
7
69
0
Order By: Relevance
“…This assumption is further supported by the specific expression signature of E/R-positive leukemias, which also suggests the involvement of other PI3K/AKT/mTOR-regulated processes, including above all cell adhesion and DNA damage response. 15,37 Pharmacological inhibition of the aberrantly activated PI3K/AKT/mTOR pathway has emerged as one of the therapeutic options for overcoming drug resistance. 13 Although E/R-positive leukemias are in general highly treatment-sensitive at initial presentation, a substantial proportion of them apparently become drug-resistant when they relapse.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is further supported by the specific expression signature of E/R-positive leukemias, which also suggests the involvement of other PI3K/AKT/mTOR-regulated processes, including above all cell adhesion and DNA damage response. 15,37 Pharmacological inhibition of the aberrantly activated PI3K/AKT/mTOR pathway has emerged as one of the therapeutic options for overcoming drug resistance. 13 Although E/R-positive leukemias are in general highly treatment-sensitive at initial presentation, a substantial proportion of them apparently become drug-resistant when they relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The RUNX genes are widely expressed, but show differential, tissue-specific expression. Although their strong homology indicates a certain degree of redundancy as observed during mouse embryogenesis (Fukushima-Nakase et al, 2005) and transcription regulation of various genes (for example Sgpp1, Ncam1, p21 WAF1 ) (Wotton et al, 2008), the RUNX proteins have been shown to perform distinct functions that are dependent on tissue type ). This review explores the dualistic associations of RUNX3 with cancer with emphasis on the emerging concept of RUNX3 as a multifunctional suppressor of solid tumors.…”
Section: Runx Family Of Transcription Factorsmentioning
confidence: 99%
“…RUNX (runt-transcription factor) transcription factors regulate genes involved in growth, survival and differentiation [103]. RUNX1 is involved in haematopoesis, RUNX2 in skeletal development, and RUNX3 in neurogenesis and gut development (reviewed in [104][105][106]).…”
Section: Runx Proteinsmentioning
confidence: 99%